(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
the purpose of training, training and teaching methods, determination of pedagogical purpose, structural components of determination of pedagogical purpose, models of determination of pedagogical purpose, levels of development of determination of pedagogical purpose, It was mentioned about the formation of training tasks.